Multi-scale segmentation of grey scale images - Olsen, Ole Fogh (1996)
Abstract: "The topic of this thesis is segmentation of grey-scale images by accessing and relating the structures of the image for all reasonable scales. Grey-scale images are regarded as physical measurements obtained by an ensemble of detectors with finite aperture and finite readout precision. Based on this point of view, the notion of image is established using linear Gaussian scale space and Morse theory. The problem of segmentation is addressed within the framework of linear Guassian scale space. The image at a given scale is partitioned according to a dissimilarity measure. Each minimum in the measure corresponds to exactly one segment. The segment is defined as the catchment basin belonging to the minimum. The gradient squared is used as the measure of dissimilarity. An essential part of the scale-space paradigm is to study the family of images indexed by scale as a family and not as a distinct set of images
Keywords: Computer graphics; Computer vision; Gaussian processes; Image processing